To dare mighty things : the life of Theodore Roosevelt - Rappaport, Doreen; Payne, C. F. (New York : Disney/Hyperion, 2013)
"This picture book biography explores the life of Theodore Roosevelt through vivid prose and the president's own words"--Provided by publisher.
School Library Journal starred, December 2013
Publisher's Weekly, September 2013
Kirkus Starred, October 2013
Includes bibliographical references.
3.1
K-3
Keywords: Roosevelt, Theodore, -- 1858-1919 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Roosevelt, Theodore, -- 1858-1919.; Presidents -- United States -- Biography; Roosevelt, Theodore, -- 1858-1919.; Presidents -- United States -- Biography; Picture books for children